Congenital Peritoneal Encapsulation with Complications: a Rare Case Report - Alam, Rezwana; Yusuf Jamil, Md Abdullah; Tanveer, Nasim; Parvin, Salma Shahnewaz; Khan, Saiful Islam; Rahman, Mizanur (Faridpur Medical College Journal, 2025)
Congenital peritoneal encapsulation is an exceptionally rare congenital anomaly characterized by the existence of an accessory peritoneal membrane that encapsulates a variable portion of the small intestine. The pathogenesis remains largely elusive; however, it is hypothesized to result from abnormal adhesions within the peritoneal lining during the physiological hernia phase of fetal mid-gut development. The phenomenon was first documented in 1868, and since then, only 45 cases have been reported in the medical literature. The condition usually remains asymptomatic and is an incidental diagnosis during surgery or autopsy. We report a case of congenital peritoneal encapsulation in a 30-years-old male who was diagnosed per operatively during laparotomy for perforation of caecum. Clinical examination revealed features of perforation, plain X-ray abdomen didn’t show free gas shadow under right dome of diaphragm and ultrasonography of the whole abdomen revealed mild free fluid in the peritoneal cavity with matted gut loops. On exploration, a large sac-like structure was found which encased the distal part of the jejunum, whole ileum, perforated caecum and part of the ascending colon. Affected portion of caecum was resected and an end ileostomy was done. Faridpur Med. Coll. J. 2025;20(1): 64-67